Experimental investigation of thermo-physical properties of tri-hybrid nanoparticles in water-ethylene glycol mixture - Anwar Ilmar, Ramadhan; Azmi, W. H.; R., Mamat (Walailak University, 2021)
In recent years, research has focused on enhancing the thermo-physical properties of a single component nanofluid. Therefore, hybrid or composite nanofluids have been developed to improve heat transfer performance. The thermo-physical properties of the Al2O3-TiO2-SiO2 nanoparticles suspended in a base of water (W) and ethylene glycol (EG) at constant volume ratio of 60:40 and different volume concentrations were investigated. The experiment was conducted for the volume concentrations of 0.05, 0.1, 0.2, and 0.3% of Al2O3-TiO2-SiO2 nanofluids at different temperatures of 30, 40, 50, 60, and 70 °C. Thermal conductivity and dynamic viscosity measurements were carried out at temperatures ranging from 30 to 70 °C by using KD2 Pro Thermal Properties Analyzer and Brookfield LVDV III Ultra Rheometer, respectively. The highest thermal conductivity for tri-hybrid nanofluids was obtained at 0.3% volume concentration, and the maximum enhancement was increased up to 9% higher than the base fluid (EG/W). Tri-hybrid nanofluids with a volume concentration of 0.05% gave the lowest effective thermal conductivity of 4.8 % at 70 °C temperature. Meanwhile, the dynamic viscosity of the tri-hybrid nanofluids was influenced by volume concentration and temperature. Furthermore, tri-hybrid nanofluids behaved as a Newtonian fluid for volume concentrations from 0.05 to 3.0%. The properties enhancement ratio (PER) estimated that the tri-hybrid nanofluids will aid in heat transfer for all samples in the present. The new correlations for thermal conductivity and dynamic viscosity of tri-hybrid nanofluids were developed with minimum deviation. As a conclusion, the combination of the enhancement in thermal conductivity and dynamic viscosity for tri-hybrid at 0.3% volume concentration was found the optimum condition with more advantage for heat transfer than other concentrations.